Health seeking behaviours among electronic waste workers in Ghana. (December 2015) - Asampong, Emmanuel; Dwuma-Badu, Kwaku; Stephens, Judith; Srigboh, Roland; Neitzel, Richard; Basu, Niladri; Fobil, Julius
Abstract Background Electronic waste workers are prone to various illnesses and injuries from numerous hazards thus the need for them to seek health care. The aim of this study was to describe health-seeking behavior, and social and other factors affecting this behavior, among electronic waste workers at Agbogbloshie, Accra, Ghana. Methods In-depth interviews were conducted and analyzed qualitatively from a grounded theory perspective. Results Workers experienced various kinds of ailments. These included physical injuries, chest and respiratory tract associated symptoms, malaria, headaches, body pains and stomach discomfort. They reported seeking health care from multiple sources, and the main determinants of health seeking behaviour were severity of illness, perceived benefit of treatment, accessibility of service, quality of service, ease of communication with service provider and cost of health care. Conclusion Multiple sources of health care were used by the e-waste workers. As cost was a major barrier to accessing formal health care, most of the workers did not subscribe to health insurance. Since enrollment in health insurance is low amongst the workers, education campaigns on the need to register with the National Health Insurance Scheme would facilitate access to formal health care and could result in improved health outcomes among e-waste workers.